Combined Therapies of Modified Taiyi Miraculous Moxa Roll and Cupping for Patients with Lumbar Intervertebral Disc Herniation. (28th March 2018) - Cai, Chunyue; Gong, Yuefeng; Dong, Dayong; Xue, Jinbiao; Zheng, Xiaoting; Zhong, Zhangfeng; Shao, Jialong; Mi, Daguo
Abstract : Lumbar intervertebral disc herniation is a kind of syndrome caused by stimulation or pressure of nerve root and cauda equina due to intervertebral disc disorder, fibrous ring rupture, and pulpiform nucleus protrusion. Application of traditional Chinese medicine (TCM) including acupuncture therapy and cupping therapy is unique and effective treatment for lumbar intervertebral disc herniation in China. Hence, we try to investigate the combined clinical efficacy of modified Taiyi miraculous moxa roll and cupping therapy on patients with lumbar intervertebral disc herniation. Seventy patients were randomly assigned into combined treatment group (n = 35 ) and control group (n = 35 ). The treatment group received combined therapy of modified Taiyi miraculous moxa roll and cupping therapy, while control group received acupuncture therapy alone. Diagnostic criteria of TCM syndrome, Japanese Orthopedic Association (JOA) score, and simplified McGill pain questionnaire (MPQ) were used to evaluate the therapy. 11 and 13 out of 35 subjects in the combined treatment group had improvement > 75% and between 50% and 75%, respectively. The corresponding number was 2 and 22 of 35 subjects in the acupuncture group. There was significant difference in the clinical efficacy between the treatment group and control group (P = 0.036 ). The scores of JOA and MPQ detected in the patients of the two groups (P < 0.05 ) also showed statistically significant differences. Moreover, no serious adverse events occurred in the patients, who received cupping therapy or acupuncture. The combined or alone therapies can effectively improve the treatment efficacy in the patients with lumbar intervertebral disc herniation, while the combined therapies show more comparative effectiveness. Furthermore, the combined therapies are potentially safe and cost-effective and also benefit the improvement of short-term pain. Therefore, the combined therapies of the two ancient TCM deserve further clinical applications.